From Broadsheet to Tabloid: Content changes in Swedish newspapers in the light of a shrunken size - Andersson,Ulrika (2013)
During the early 2000s, the newspaper market in Northern Europe was characterised by a trend of format changes as many broadsheets have chosen to adapt to the tabloid format. Similar tendencies also have emerged in other Western countries, making it a transnational phenomenon. Critics have argued that a reduced size impacts the content, resulting in increased tabloidisation, finding a connection between the page size and the news content whereby the broadsheet and tabloid formats require different kinds of journalism. Thus, this study aims to analyse whether it is possible to detect this type of increased tabloidisation in relation to the resizing of newspapers. Using the theoretical concept of tabloidisation, this study begins with a content analysis of Swedish dailies that have changed their format during the early 2000s. Comparisons are made to newspapers that did not undergo this type of transition as means of determining whether any of the changes detected can be explained by the actual format change, or rather, are the effects of other factors. The study focuses on news content published in 1990, 2000, and 2010. It reveals that the format itself has had only a minor influence on journalism, in that all newspapers show similar signs of increased tabloidisation during this period.